Product market regulation, firm size, unemployment and informality in developing economies - Olivier Charlot; Franck Malherbet; Cristina Terra (Institute for the Study of Labor (IZA), 2011)
This paper studies the impact of product and labor market regulations on informality and unemployment in a general framework where formal and informal firms are subject to the same externalities, differing only with respect to some parameter values. Both formal and informal firms have monopoly power in the goods market, they are subject to matching friction in the labor market, and wages are determined through bargaining between large firms and their workers. The informal sector is found to be endogenously more competitive than the formal one. We find that lower strictness of product or labor market regulations lead to a simultaneous reduction in informality and unemployment. The difference between these two policy options lies on their effect on wages. Lessening product market strictness increases wages in both sector but also increases the formal sector wage premium. The opposite is true for labor market regulation. Finally, we show that the so-called overhiring externality due to wage bargaining translates into a smaller relative size of the informal sector.
urn:nbn:de:101:1-201104113925
Keywords: E24; E26; J60; L16; O1; 330; informality; product and labor market imperfections; firm size; Regulierung; Arbeitsmarktpolitik; Wirkungsanalyse; Informeller Sektor; Arbeitslosigkeit; Lohnstruktur; Unvollkommener Markt; Entwicklungsländer